A Comparison of Palpation Technique versus Ultrasound-Guidance for Arterial Line Placement by Residents in a Teaching Institution - Khan, Taimur Azam; Ali Shah, Syed Qasim; Riaz, Muhammad Mohsin; Mateen, Osama Abdul; Beg, Mirza Hamid; Sharif, Muhammad Huzaifa (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the ease of placement of arterial catheters using palpation versus ultrasound guidance under aseptic measures. Study Design: Quasi-experimental study. Place and Duration of Study: Combined Military Hospital, Rawalpindi Pakistan, from Feb to Aug 2022. Methodology: Patients of either gender, aged 18 to 90 years presenting to a paranesthesia clinic that required intra-arterial blood pressure monitoring were included in the study. After induction, under General Anaesthesia, arterial lines were placed following an aseptic technique using ultrasound or palpatory method; in Group-U (ultrasound) or Group-P (Palpation),respectively. Demographic variables of the patient along with hemodynamic readings and success rate at first or multiple attempts, along with the total time of cannulation, were recorded. Results: Out of the total 74 patients, 59(79.7%) patients belonged to ASA-1 Grade, and 15(20.3%) patients in ASA-2 Grade. The mean age of the patients was 48.3±16.3, while mean BMI was 25.42±2.8kg/m2. In Group-P, the first-pass success was achieved in 19(51.4%) patients as compared to 32(86.5%) in Group-U when ultrasound was used (p<0.05). Conclusion: The success rate in placing an arterial line using ultrasound was significantly greater than the conventional palpatory method. Therefore, ultrasound should be a preferred modality during intra-arterial line placement.